Identification of volatile organic compound of oil palm plants infected with Ganoderma sp. - Irma Kresnawaty; Agustin Sri Mulyatni; Deden Dewantara Eris; Tri Panji; Happy Widiastuti; Kuwat Triyana (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2024)
The success of controlling basal stem rot (BSR) disease caused by Ganoderma sp. is mostly determined by the early detection of the fungi. Hence, when the signs of infection begin to appear, plants are generally difficult to rescue since the pathogen infection has spread widely to all parts of the plant. Therefore, early detection through the application of biosensors for Ganoderma sp. infection is absolutely necessary. This study aim was to identify biomarker compounds of Ganoderma sp. infection in oil palm plants with GC-MS for volatile compounds, and LC-MS for non-volatile compounds. The results showed that Ganoderma sp. mycelium produced pyrimidinamine compounds. Meanwhile in early infected nursery plants, were found benzo[h]quinoline, hexaoxa-7,9,11-trisilaheptad, tris-(trimethyl-silyl ester and methyl-tris(trimethyl-siloxy)-silane). Whereas in Bekri, Rejosari, and Adolina plantation, the compound methyl-tris(trimethyl-siloxy)-silane was also found in healthy mature plants. GC-MS test results showed that for early, moderate and severe plants produced several benzene derivative compounds such as ethylbenzene, xylene, and benzaldehyde. These compounds were assumed to be resulted from the breakdown of the lignin structure which build plant cell walls, and have potency to be used as marker compounds for early infected Ganoderma sp. detection. The result of the produced gas quantification concluded that in the produced oil palm plants released less CO2 compared to healthy plants. On the other hand, the NH3 produced was higher than the healthy plants. Meanwhile, two non-volatile compounds were found that they were only produced by infected trunk and root tissue, namely pseudobrucine and picrasidine.